2012
DOI: 10.1164/rccm.201107-1332oc
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Red Blood Cell Transfusion and Short-Term Pulmonary, Immunologic, and Coagulation Status

Abstract: Rationale: Transfusion-related pulmonary complications are leading causes of morbidity and mortality attributed to transfusion. Observational studies suggest an important role for red blood cell (RBC) storage duration in these adverse outcomes. Objectives: To evaluate the impact of RBC storage duration on shortterm pulmonary function as well as immunologic and coagulation status in mechanically ventilated patients receiving RBC transfusion. Methods: This is a double-blind, randomized, clinical trial comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 59 publications
1
77
1
5
Order By: Relevance
“…Of the 16 trials included in the recent Cochrane review, 25 we judged 6 to be ineligible 36-41 because they did not report the outcomes examined in this review, leaving a total of 12 eligible studies. 26,27,37,[42][43][44][45][46][47][48][49][50] Agreement (k) for the title and abstract screening was 0.73, and for the completed full-text screening 0.71. Inter-rater agreement on individual domains of the risk of bias tool ranged from 0.51 to 0.69.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 16 trials included in the recent Cochrane review, 25 we judged 6 to be ineligible 36-41 because they did not report the outcomes examined in this review, leaving a total of 12 eligible studies. 26,27,37,[42][43][44][45][46][47][48][49][50] Agreement (k) for the title and abstract screening was 0.73, and for the completed full-text screening 0.71. Inter-rater agreement on individual domains of the risk of bias tool ranged from 0.51 to 0.69.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from 12 randomized controlled trials 26,27,37,[42][43][44][45][46][47][48][49][50] that included patients with varying ages and experiencing a range of medical and surgical conditions found no benefit when fresher RBCs were transfused as opposed to older/standard-issue RBCs for either mortality ( Figure 3 and Table 2) or adverse events ( Figure 4 and Table 2). Results suggested that, if anything, fresher RBCs might lead to an increase rather than a decrease in nosocomial infections ( Figure 5 and Table 2).…”
Section: Main Findingsmentioning
confidence: 99%
“…Despite these numerous studies which suggest that the use of fresher blood for transfusions could be potentially beneficial, a randomized control trial did not find a difference in outcome between the use of a single unit of fresh blood and a single unit of stored blood when assessing pulmonary, inflammatory and coagulation markers [33].…”
Section: Clinical Relevancementioning
confidence: 93%
“…The quality and efficacy of RBC storage may have significant impact on the occurrence and pathogenesis of TRALI [33,34]. The current standard of duration of storage of red blood cells (RBCs) by the American Association of Blood Banks is a maximum of 6 weeks (42 days) of storage [35].…”
Section: Red Blood Cell Storage and Tralimentioning
confidence: 99%
See 1 more Smart Citation